Ammonia and toluene vapour sensing characteristic of chitosan films - Mohd Hafiz Zainol (School of Material Engineering, Universiti Malaysia Perlis, 2013)
The study on the chitosan film sensor properties to ammonia and toluene vapour in range of 0.5cc to 2cc of concentrations was carried out at room temperature (~27- 31p0sC). The effect of different chitosan concentration, deposition time and deposition voltage on sensing properties of the sensor was investigated.